Coming to terms with the North. Scandinavia in Polish culture at the turn of the 21st century - Czapliński, Przemysław (Folia Scandinavica Posnaniensia, 2023)
The article deals with representations of Scandinavia in Polish literature from the 1980s to the second decade of the 21st century. The basic claim of the article is that a shift in the Polish imagination from the West to the North has occurred through literature and growing public interest. This shift began with efforts to transform the initial stereotype of Scandinavia as a land of prosperity. In subsequent stages, the imaginary was expanded by literature to include the themes of equality, social trust and self-correcting modernity. Complicating the image of Scandinavia made it into a viable alternative to Western modernity.